Improvement plan to reduce the operating costs of an agro-industrial milling company [Plan de mejora para reducir los costos operativos de una empresa agroindustrial molinera] - De la Cruz, Caroline (2021)
This study was performed in an agro-industrial milling company with the aim of reducing operative costs over the production and manteinance areas. The company's data was obtained through an interview and documentary analysis. Initial diagnosis was made using the following methods: SWOT analysis, Porter's five forces, PESTLE analysis, IFE and EFE Matrix, Ishikawa diagram and Pareto chart. An improvement plan was designed including tools related to Production Management and Manteinance Management: Demand Forecasting, MRP, Preventing Manteinance Plan, Transport network optimization, SRM and Process Standarizing. The improvement plan was simulated in ProModel 2016 software, using projected production data from the development of the proposed tools. Results obtained were: removal of rate of unscheduled plant shutdown, 14% decreased of the production rate not achieved by the machine "Table Paddy" and 9% decreased of the rate of unused capacity; obtaining 54.65% total reduction of the operating costs analyzed. The profitability of the improvement plan was demonstrated with a NPV of S/ 87,052.97 and an IRR of 69%.